Ultrasound Irradiation Assisted Synthesis of Luminescent Nano Amide-Functionalized Metal-Organic Frameworks; Application Toward Phenol Derivatives Sensing - Yan, Xiao-Wei; Gharib, Maniya; Esrafili, Leili; Wang, Su-Juan; Liu, Kuan-Guan; Morsali, Ali (Frontiers in Chemistry, 2022)
Two nano amide-functionalized metal-organic frameworks (MOFs) with molecular formula [Co(oba)(bpta)]•(DMF)2 TMU-50 and [Co2(oba)2(bpfn)]•(DMF)2.5 TMU-51 obtained under ultrasonic method without any surfactants. The only difference between the two selected amide functionalized pillar ligands, N,N′-bis(4-pyridinyl)-terephthalamide (bpta), and N,N′-bis-(4-pyridylformamide)-1,5-naphthalenediamine (bpfn), is related to the naphthyl group, which led to the different luminescence properties of the nano frameworks. In this study, special ability of the luminescent nano MOFs were investigated to sensitize nitroaromatic compounds. Nano TMU-50 owning to its unique and porous framework, shows a good sensitivity towards nitro phenol by strong fluorescence emission with detection limit of 2×10-3 mM-1. Both nano MOF structures were characterized via many analyses such as Field Emission Scanning Electron Microscopy (FE-SEM), powder X-ray diffraction, elemental analysis (EA), and FTIR spectroscopy. Moreover, the effect of a number of important parameters including: initial reagent concentrations, power of ultrasound and time on features of nano structures were examined. According to fluorescence titration results, the activated nano-TMU-50 detected NP selectively with a quick response.